Integrasi Pelaporan Keuangan sebagai implementasi Good Governance pada Baitul Mal Masjid Baitul Arqam Sumampir - Hijroh Rokhayati; Uswatun Hasanah; Poppy Dian Indira Kusuma (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2023)
The weakness of the information system at the Baitul Maal Masjid Baitul Arqam (BM-MBA) is an obstacle in reporting activities and financial reporting that is transparent and accountable. Knowledge of good financial governance in accordance with the principles of good governance has not been owned by the BM-MBA manager. It takes the active role of academics to increase the knowledge of BM-MBA managers. The Community Service Program (PkM) aims to build synergy between the servants (UNSOED lecturers) and MBA takmir to improve BM-MBA services in the digital economy era. The target audience for this PkM program are BM-MBA managers and MBA congregations as recipients of BM-MBA services. The stages in the implementation of the PkM program began with pre-survey activities, formulating methods for solving partner problems, counseling and mentoring, finally evaluation.